2000
DOI: 10.4049/jimmunol.165.6.3430
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Inducible Nitric Oxide Synthase Results in Reduced Atherosclerosis in Apolipoprotein E-Deficient Mice

Abstract: Inducible NO synthase (iNOS) present in human atherosclerotic plaques could contribute to the inflammatory process of plaque development. The role of iNOS in atherosclerosis was tested directly by evaluating the development of lesions in atherosclerosis-susceptible apolipoprotein E (apoE)−/− mice that were also deficient in iNOS. ApoE−/− and iNOS−/− mice were cross-bred to produce apoE−/−/iNOS−/− mice and apoE−/−/iNOS+/+ controls. Males and females were placed on a high fat diet at the time of weaning, and ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(136 citation statements)
references
References 45 publications
3
132
0
Order By: Relevance
“…A more recent report confirms our results that iNOS deficiency reduces atherosclerosis in apoE-KO mice. 33 Our study differs, however, because we assayed en face lesion area as opposed to aortic root lesions, we used animals that were all backcrossed to the C57BL6 strain, and we provide data about levels of plasma MDA-TBA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report confirms our results that iNOS deficiency reduces atherosclerosis in apoE-KO mice. 33 Our study differs, however, because we assayed en face lesion area as opposed to aortic root lesions, we used animals that were all backcrossed to the C57BL6 strain, and we provide data about levels of plasma MDA-TBA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages also serve as the source of other inflammatory mediators contributing to the development of endometriosis, including NO. NO produced in abundance by the inducible form of NO synthase (iNOS, NOS2), induced by oxidant-sensitive transcription factors like NFkB, has the potential to exacerbate endometriosis by promoting inflammation and necrosis at the site of lesion (Beckman & Koppenol 1996, Detmers et al 2000. Moreover, the peritoneal accumulation of pro-oxidant and pro-inflammatory factors during retrograde menstruation, such as hemoglobin and its by-product heme, may cause OS-mediated mesothelial layer damage and chronic inflammation, permitting the attachment and development of endometrial fragments in the peritoneum.…”
Section: Iron-induced Peritoneal Os In Endometriosis Developmentmentioning
confidence: 99%
“…Analysis of transgenic mice that lack or overexpress NO synthases indicated that NO exerts both protective (4,5) and atherogenic (6)(7)(8)(9) effects. The double role of NO might explain why NO-generating drugs (e.g., glyceryl trinitrate) have not been reported to limit the progression of atherosclerosis in humans.…”
mentioning
confidence: 99%